2012
DOI: 10.1016/j.jenvman.2012.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Rendering wastes obtained from gold analysis by the lead-fusion fire-assay method non-hazardous

Abstract: The classical method of melting lead by fire-assay (Pb-FA) is the most frequently used analytical technique in gold prospection. The crucible solid waste which is generated in this process is usually characterized by chemical and mineralogical composition, granulometric size distribution, and classified according to Brazilian Environmental Regulations. This study demonstrates how acid leaching can be used to remove lead from waste originally classified as hazardous by treatment with hydrochloric and nitric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In a previous work (Magalhães et al, 2012), we found that 0.09% of PbO by weight was incorporated into the crucible waste, which was also classified as hazardous, according to the limits established by Norm ABNT NBR 10004 (ABNT, 2004a). After extraction of such waste with hydrochloric and nitric acids followed by chemical precipitation with sodium metasilicate solution, 99.9% (w/w) of lead was recovered, rendering the ultimate waste non-hazardous.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work (Magalhães et al, 2012), we found that 0.09% of PbO by weight was incorporated into the crucible waste, which was also classified as hazardous, according to the limits established by Norm ABNT NBR 10004 (ABNT, 2004a). After extraction of such waste with hydrochloric and nitric acids followed by chemical precipitation with sodium metasilicate solution, 99.9% (w/w) of lead was recovered, rendering the ultimate waste non-hazardous.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were analyzed at the Chemical Metallurgical Laboratory JV Metals, located in El Pache, Portovelo, Ecuador. The method used to determine the head grade (feet) of the mineral sample was the Fire Assay [31]. This method consists of melting the sample with reagents and fluxes to detect metals such as gold and silver.…”
Section: Sampling and Data Analysismentioning
confidence: 99%
“…However, PbFA is accompanied by significant occupational safety and health (OSH) 7 and waste disposal 8 concerns, which arise mostly from the large amounts of PbO required: up to tonnes per month in large commercial laboratories. Reagentless options such as neutron 9 and gamma 10 activation analyses have been used to quantify gold directly in ores but their application in commercial mineral assay laboratories is seldom practicable.…”
Section: Accepted Manuscriptmentioning
confidence: 99%